The quest for security : protection without protectionism and the challenge of global governance - Stiglitz, Joseph E.; Kaldor, Mary (Columbia University Press, 2013)
The essays in this collection boldly confront the quest for security arising out of the social, economic, environmental, and political crises and transformations of our century. Joseph E. Stiglitz and Mary Kaldor begin with an expansive, balanced analysis of the global landscape and the factors contributing to the growth of insecurity. While earlier studies have touched on how globalization has increased economic insecurity and how geopolitical changes may have contributed to military insecurity, this volume looks for some common threads: in a globalized world without a global government ...